IMPROVING NUMBER RECOGNITION 1–5 THROUGH INTERACTIVE DIGITAL LEARNING MEDIA FOR GROUP A KINDERGARTEN CHILDREN LIUNGGUNUNG - Zhafira Fartimatuzahra Hidayat; Anisa Purwani; Rika Purnamasari, (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This classroom action research aimed to improve the ability of group A kindergarten children to recognize numbers 1–5 through interactive digital learning media. The study was conducted due to the low level of children’s skills in identifying numerical symbols correctly. The subjects were 11 children in group A at UPTD TK Pembina Liunggunung during the second semester of the 2025/2026 academic year. The research method applied was Classroom Action Research (CAR), carried out in two cycles, each consisting of planning, implementation, observation, and reflection. Data collection instruments included observation sheets and field notes. The results showed a significant improvement in children’s cognitive abilities in number recognition. In the initial condition, only 36% of the children were able to recognize numbers 1–10 correctly. After the first cycle, this figure increased to 64%, and by the second cycle, it reached 91%. These findings indicate that interactive digital learning media are effective in enhancing early childhood cognitive skills, especially number recognition. Therefore, interactive digital media can be considered a relevant alternative for teachers in supporting cognitive learning in kindergarten group A.